1989
DOI: 10.1111/j.1476-5381.1989.tb16865.x
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic pharmacology of tetrahydroaminoacridine in vivo and in vitro

Abstract: 1 The effect of tetrahydroaminoacridine (THA) on cholinergically mediated behaviour in the rat and mouse has been investigated. In addition the actions of this compound on cholinesterase activity and on muscarinic and nicotinic receptors has also been examined. 2 Administration of THA (5-20mgkg-1, i.p.) produced a dose-dependent increase in tremor, hypothermia and salivation in both rats and mice. A similar profile of activity was seen following physostigmine (0.1-0.6 mg kg -1) administration. 3 THA was approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…It has also been reported that nicotine will stimulate striatal 5-HT release (Westfall et al, 1983). In addition to its inhibitory activity against AChE (Shaw & Bentley, 1953;Steinberg et al, 1975) THA is centrally active at both muscarinic and, more weakly, at nicotinic receptors (Nilsson et al, 1987;Hunter et al, 1989;Perry et al, 1988;Pearce & Potter, 1988). It was feasible therefore that THA might modulate monoamine release via ACh receptors, either through a direct action or by increasing the concentration of ACh.…”
Section: Effect Of Tha On S-ht Reuptakementioning
confidence: 99%
“…It has also been reported that nicotine will stimulate striatal 5-HT release (Westfall et al, 1983). In addition to its inhibitory activity against AChE (Shaw & Bentley, 1953;Steinberg et al, 1975) THA is centrally active at both muscarinic and, more weakly, at nicotinic receptors (Nilsson et al, 1987;Hunter et al, 1989;Perry et al, 1988;Pearce & Potter, 1988). It was feasible therefore that THA might modulate monoamine release via ACh receptors, either through a direct action or by increasing the concentration of ACh.…”
Section: Effect Of Tha On S-ht Reuptakementioning
confidence: 99%
“…In the case of reversible cholinesterase inhibitors such as tacrine and donepezil, inhibition of enzyme activity can be partially reversed by dilution, because of dissociation of the inhibitor from the enzyme with time (Hunter et al, 1989;Dawson, 1990;Kosasa et al, 2000). Furthermore, using microdialysis, it is reported that donepezil dose-dependently increases the extracellular acetylcholine concentration in rats (Kawashima et al, 1994;Kosasa et al, 1999) and in monkey (Tsukada et al, 2004), which may cause additional AChE inhibition (substrate inhibition) (Reiner and Radic, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The drug exerts diverse effects [3,4]. Some of them are not related to the cholinergic system [5,6] and may underlie various side effects. Tacrine molecule freely penetrates through cell membranes [7].…”
Section: Introductionmentioning
confidence: 99%